Lipopolysaccharide Reverses Hepatic Stellate Cell Activation Through Modulation of cMyb, Small Mothers Against Decapentaplegic, and CCAAT/Enhancer‐Binding Protein C/EBP Transcription Factors. Issue 5 (22nd October 2020) - Sharma, Akanksha; Verma, Alok K.; Kofron, Matthew; Kudira, Ramesh; Miethke, Alexander; Wu, Tong; Wang, Jiang; Gandhi, Chandrashekhar R.
Abstract : Background and Aims: During liver injury, quiescent hepatic stellate cells (qHSCs) transdifferentiate into proliferative and fibrogenic activated myofibroblastic phenotype (activated hepatic stellate cell; aHSCs) expressing smooth muscle α‐actin (αSMA) and platelet‐derived growth factor beta receptor (PDGFβR). Their interactions with gut‐derived bacterial lipopolysaccharide (LPS) are implicated in hepatic fibrogenesis. However, LPS can also attenuate fibrogenic characteristics of aHSCs. Approach and Results: We examined molecular mechanisms of antifibrogenic effects of LPS on aHSCs in vitro and in vivo . Culture‐activated rat HSCs were exposed to 0‐100 ng/mL of LPS or its active component, diphosphoryl‐lipid A (DPLA), and parameters of fibrosis and inflammatory cytokines/chemokines were determined by qRT‐PCR, western, and immunohistochemical analyses. In vivo, HSCs were activated by repeated CCl4 administration to rats every 3 days for 3 or 8 weeks, then challenged with LPS (5 mg/kg; IP). HSCs were isolated 24 hours later, and fibrogenic/inflammatory parameters were analyzed. LPS induced phenotypic changes in aHSCs (rounding, size reduction) and loss of proliferation. LPS down‐regulated expression of αSMA, PDGFβR, transforming growth factor beta receptor 1 (TGFβR1), collagen 1α1 (Col1α1), and fibronectin while up‐regulating tumor necrosis factor alpha, interleukin‐6, and C‐X‐C motif chemokine ligand 1 expression. LPS did not increase peroxisome proliferation‐activated receptor gamma expression or lipid accumulation typical of qHSCs. DPLA elicited the same effects as LPS on aHSCs, indicating specificity, and monophosphoryl lipid A down‐regulated fibrogenic markers, but elicited very weak inflammatory response. LPS down‐regulated the expression of cMyb, a transcription factor for αSMA, and up‐regulated small mother against decapentaplegic (SMAD)7 and CCAAT/enhancer‐binding protein (C/EBP)δ, the transcriptional inhibitors of Col1α1 expression. In vivo LPS treatment of aHSCs inhibited their proliferation, down‐regulated PDGFβR, αSMA, TGFβR1, Col1α1, and cMyb expression, and increased expression of SMAD7, C/EBPα, and C/EBPδ. Conclusions: In conclusion, LPS induces a unique phenotype in aHSCs associated with down‐regulation of key fibrogenic mechanisms and thus may have an important role in limiting fibrosis.